Different Heschl’s Gyrus Duplication Patterns in Deficit and Non-deficit Subtypes of Schizophrenia - Takahashi, Tsutomu; Sasabayashi, Daiki; Takayanagi, Yoichiro; Furuichi, Atsushi; Kobayashi, Haruko; Noguchi, Kyo; Suzuki, Michio (Frontiers in Psychiatry, 2022)
Deficit syndrome schizophrenia is a characteristic subtype defined by persistent negative symptoms and poor functional outcomes; however, the biological mechanisms underlying this specific subtype have not yet been elucidated in detail. The present magnetic resonance imaging study examined the prevalence of duplicated Heschl’s gyrus (HG), a potential neurodevelopmental marker, in schizophrenia patients with (N = 38) and without (N = 37) the deficit syndrome. The prevalence of the HG duplication pattern bilaterally was higher in the whole schizophrenia group than in 59 matched healthy controls. Furthermore, the prevalence of right HG duplication was significantly higher in the deficit schizophrenia group than in the non-deficit schizophrenia group. The HG pattern in schizophrenia was not associated with clinical variables, including illness duration, medication, and symptom severity, while right HG duplication correlated with higher scores for Proxy for the Deficit Syndrome. The present results suggest that the prominent neurodevelopmental pathology associated with gyral formation of HG may contribute to enduring negative symptomatology in schizophrenia.